Identification of Skeletal Deformities in Far Eastern Catfish, Silurus asotus under Indoor Aquaculture Condition - Yang, Won Seok (Dev Reprod, 2015)
For the 2 years of farming, at the indoor circulating aquaculture system, four kinds of skeletal deformities were found among 60 Far Eastern catfish, Silurus asotus. Deformities saw jawbone’s luxation, abnormality of upper lip and malocclusion. Spinal deformity was most fatal deformities with low weight and small length. Jawbone’s luxation had 1 maxilla and 2 mandibles. Abnormality of upper lip had just lip was back over. Malocclusion’s left maxilla and right maxilla were not balanced. This experiment was any deformities in this species through the deformity can grasp how it affects.